KETAHANAN UMKM FROZEN FOOD “WISNA FRESH” KABUPATEN PONOROGO MELINTASI PANDEMI COVID 19 - Wijianto Wijianto; Ika Farida Ulfah; Ardyan Firdausi Mustoffa (Al-Buhuts, 2021)
The COVID-19 pandemic caused the economy in Indonesia to experienceacrisis,one of which is micro and medium-sized small businesses in the culinary sector experienced a drastic decline”. “As a result of the enactment of the government policies, namely Large-Scale Social Restrictions (PSBB), many of the culinary businesses musttwisttheir brainsso that their efforts cansurvive this the pandemic”. “This is achallenge for the government to provide assistance subsidies to MSME actors, but in the minister him self many MSMEs in the culinary sector make their own ideas by utilizing Technology of social media as a bridge to keep his business running”. “For this reason,better strategies are a needed to maintain MSMEs in Ponorogo across COVID-19”. This research is to find out how the marketing strategy that has been done by MSMEs wisna fresh to increase sales of products . This study uses qualitative descriptive methods where data is obtained by conducting interviews. This research uses SWOT analysis to take advantage of opportunities and maximize strengths, reduce weaknesses and avoid threats.  The results of the research showed that the marketing strategy carried out by WISNA FRESH MSMEs is a marketing mix consisting of product, price, place, promotion, process, people, physical evidence (7P). And the marketing strategy implemented by MSMEs Wisna Fresh is Segmentation, Targetting, Positioning or commonly called STP. From the marketing strategy implemented, it affects the sales of WISNA FRESH MSMEs so as to improve the sales of their products, but in this study found obstacles that many employees of mothers often ask permission to accompany or pick up children this will also affect production activities, hence the need for SOP (Standard Operating Procedures) to help for the smooth and resilience of the company in the pandemic period.